Mise à jour au sujet des frais de scolarité : Le gouvernement choisit une voie susceptible de ruiner les universités anglophones du Québec - Quebec Community Groups Network (QCGN) (2023)

Community Vitality & Acceptability of English Canadian Migrants Rated by Québecois Francophone, Acadian and Franco-Ontarian University Students - Bourhis, Richard Y.; Sioufi, Rana; Allard, Réal (QUESCREN Education and Vitality Forum 2023, 2023)

Senate Standing Committee on Social Affairs, Science and Technology : Study on Bill C-35, An Act respecting early learning and child care in Canada - Quebec Community Groups Network (QCGN) (2023)

QCGN Statement on Appointment of New Parliamentary Secretaries - Quebec Community Groups Network (QCGN) (2023)

Three Approaches to Writing School Programs with Official Language Minorities : Research Brief no. 9 - Gani, Raphaël (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes Randy Boissonnault as the new Federal Minister of Official Languages - Quebec Community Groups Network (QCGN) (2023)

Senate Standing Committee on Official Languages (OLLO) : Study of C-13 An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2023)
The QCGN has participated in every step of the modernization of the Official Languages Act, beginning with Bill S-209; an initiative of this Chamber led by the Honourable Maria Chaput. English-speaking Quebec worked closely and in good faith with our Francophone counterparts in the rest of Canada, Ministers of Canadian Heritage and Official Languages and this Committee during its historic study to modernize the Act, beginning in 2017.

Producing Regulations for Part VII of the Official Languages Act : English-speaking Quebec’s Stake in the Process - Quebec Community Groups Network (QCGN) (2023)